FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Yulia, 09.05.52.0072 (Students Journal of Accounting and Banking, 2013)
The objective of this study is to examine the influence of size, type industry, profitability, leverage, managerial ownership, corporate social responsibility among LQ45 which listed on Indonesia Stock Exchange. Company size dividend witg using natural logaritma total asset, type industry measured by industry classification, profitability dividend with ratio between tax profit with asset totally, leverage measured by the ratio of total debt to total capital and managerialÂ ownership measured by shares held managerial.The population is companies which listed in LQ45 on indonesia stock exchange at period 2010-2012. Sample was choose using purposive sampling method amount to 29 companies. Technique test of data is by using multiple linear regression.These results indicatethat profitability is significant positively influence the corporate social responsibility disclosure. Thus, the result of those test provide support for the hypothesized.Size, type industry, leverage, managerial ownership, isnât influence the corporate social responsibility disclosure at all.Keywords: size, profile, profitability, leverage, managerial ownership and corporate social responsibility disclosure.